BIOTYPING AND MOLECULAR DETECTION OF STREPTOCOCCUS MUTANS AND STREPTOCOCCUS SOBRINUS IN CARIES ACTIVE SUBJECTS - KHALID IMRAN,; R. SENTHILKUMAR, (International Journal of Pharma and Bio Sciences, 2014)
Dental caries is one of the most common prevailing disease in humans and a significant public health problem worldwide. Mutans streptococci are a group of oral bacteria, among this group Streptococcus mutans and Streptococcus sobrinus are frequently associated with dental caries. The aim of the present study was (i) To investigate the reliability of morphological, biochemical and multiplex PCR based methods to differentiate S. mutans and S. sobrinus (ii) To determine the proportion of S. mutans, S. sobrinus and their biotypes present in caries subjects. Dental plaque samples were collected from caries subjects and cultured on Mitis Salivarius Bacitracin agar. The bacteria were identified based on colony morphology, biotyping and multiplex PCR. The results showed that the multiplex PCR was found to be a simple and reliable method for detection and differentiation of S. mutans and S. sobrinus when compared to morphological and biotyping methods. The proportion of S. mutans (65.78%) were higher than S. sobrinus (21.05%) and biotype I (60.52%) was most frequently isolated from the study population.